A compact 4T1M2C AMOLED pixel circuit with multimodal drive transistor - Eva Bestelink; Radu A. Sporea (Journal of Information Display)
We propose a 5-transistor, 2-capacitor (5T2C) AMOLED pixel circuit using a multimodal transistor (MMT) as driver, which may be more appropriately referred to as 4T1M2C to reflect the inclusion of a device which is distinctly different from conventional Ohmic-contact thin-film transistors (TFTs). The MMT is a type of contact-controlled transistor, here implemented with a Schottky source. Its gating mechanisms separate ‘analog' charge injection, controlled by the source contact, from ‘digital' channel conductance switching. The mixed-signal operation of the MMT allows it to perform the function of multiple conventional transistors in a power- and area-efficient manner, enabling pixel circuit design to achieve superior image uniformity and energy efficiency, due to the combination of threshold compensation scheme and inherent saturation properties of the MMT drive transistor.